ARCHITECTURAL PARADIGM OF THE INTERACTIVE INTERFACE MODULE IN THE CLOUD TECHNOLOGY MODEL - RATOV, Denis (Applied Computer Science, 2020)
The article discusses an architectural template for building a module for organizing the work of a multiuser windowed information web-system. To solve this problem, JavaScript objects have been created: a window manager object and a window interactive interface class, which allow a web application to function when organizing cloud technologies. The software implementation is considered and the results of the practical use of the developed module are presented.